Trends and opportunities for greener and more efficient microbially induced calcite precipitation pathways: a strategic review - Bhadiyadra, Kishan; Jong, Siaw Chian; Ong, Dominic E L; Doh, Jeung-Hwan (Geotechnical research, 2024)
Microbially induced carbonate precipitation (MICP) is extensively used for soil stabilisation, sand erosion control, bioremediation and concrete repair. However, detailed bibliometric studies on MICP are scarce, particularly regarding industrial feedstocks, such as urea for ureolytic bacteria and calcium chloride, and the associated ammonia gas production, which poses challenges for large-scale applications. This study reviews 857 articles from the Scopus database (2000–2024), using the VOSviewer software to visualise data on publications, citations, authors, countries, journals, trending keywords and research topics. Significant global collaboration is evident, led by China and the USA. The most cited papers discuss ureolytic microorganisms enhancing soil properties, the basic MICP process, reducing concrete damage, improving soil and groundwater systems and the impacts of MICP on urea hydrolysis and ammonia production. Key terms such as ‘calcium carbonate’, ‘ammonia’ and ‘Sporosarcina pasteurii’ are central to MICP research. Co-occurrence analysis highlights thematic clusters such as microbial cementation and geological features, emphasising the multidisciplinary role of MICP in tackling environmental problems. This review highlights the need to mitigate environmental impacts, particularly those of ammonia production and energy use, in ureolytic MICP. Life-cycle assessments reveal that while ureolytic MICP reduces carbon dioxide emissions, it often consumes more energy, necessitating alternative nutrient sources and cost-effective practices for large-scale applications.